Material characterizations of high refractive films for active waveguide - Kantisara Pita. (2008)
The fabrication of SiON and Erbium (Er) doped SiON films have been successfully developed using the sputtering and co-sputtering techniques. The properties of the films such as the optical properties, the compositions, the chemical bonds and the microstructures, have been well characterized and studied using the spectroscopy ellipsometry, Rutherford Backscattering, Fourier Transform Infrared and Raman spectroscopy/XRD measurements respectively. Low optical films with desired refractive index, in the range of 1.47 – 1.81 at 1550 nm, and compositions can be easily fabricated.